Chemotherapy-associated paronychia treated with a dilute povidone-iodine/dimethylsulfoxide preparation - Capriotti K; Capriotti JA (Dove Medical Press, 2015)
Kara Capriotti,1,2 Joseph A Capriotti1,3 1ALC Therapeutics, LLC, Springhouse, PA, 2Bryn Mawr Skin and Cancer Institute, Rosemont, PA, 3Plessen Ophthalmology Consultants, Christiansted, VI, USA Background: Nail changes associated with chemotherapy in general, and particularly with taxane and epidermal growth factor receptor inhibitor-based regimens, are common presentations in our clinical population. Currently, there are no consensuses about therapies supported by clinical trials nor are there any US Food and Drug Administration-approved treatments for this indication. Findings: A 42-year-old woman with stage 2A breast cancer presented to our clinic with chemotherapy-induced paronychia. Symptoms were severe enough that cessation of chemotherapy was being considered. The patient's chemotherapy regimen included doxorubicin, cyclophosphamide, and docetaxel. Conclusion: The topical povidone-iodine/dimethylsulfoxide system is very effective in alleviating the signs and symptoms of severe paronychia associated with chemotherapy. This novel combination warrants further investigation in randomized, controlled trials to further elucidate its clinical utility. Keywords: paronychia, chemotherapy, breast cancer, povidone-iodine, dimethylsulfoxide